The Actual Independence of Regulatory Agencies in Brazil - Sampaio, Paulo Soares (Law, State and Telecommunications Review, 2013)
Purpose ”“ This article analyses the “formal” and the “actual” independence of regulatory agencies in Brazil, considering the several aspects of their structure. Methodology/approach/design ”“ This study is based on historical, doctrinal and institutional perspectives in comparative law designed to frame the concepts of regulation and regulatory agencies, by analyzing features of legitimation and control in a country characterized by the existence of the rule of law. The article adopts the format of review of the literature. Findings ”“ This study concludes that the transplant of legal structures that support the independence of regulatory agencies from abroad has low efficiency in the pre-existing normative and political cultures, what may lead to a reduction of their actual independence. Practical Implications ”“ It serves as groundwork for researchers interested in the relationships between regulation theories and the history of regulatory agencies in Brazil. Originality/value ”“ This article presents a synthesis of the concepts related to regulation and regulatory agencies, and their evolution in the United States and Brazil, focusing on formal and actual independence issues. The recent bill regarding regulatory agencies under scrutiny in the Brazilian Congress and the dilemma between the independence of regulatory agencies and the federal government agenda are also presented in this article.